Combined Modality Therapies for High-Risk Prostate Cancer: Narrative Review of Current Understanding and New Directions - Greenberger, Benjamin A.; Chen, Victor E.; Den, Robert B. (Frontiers in Oncology, 2019)
Despite the many prospective randomized trials that have been available in the past decade regarding the optimization of radiation, hormonal, and surgical therapies for high-risk prostate cancer, many questions remain. There is currently a lack of level 1 evidence regarding the relative efficacy of radical prostatectomy (RP) followed by adjuvant radiation compared to radiation therapy (RT) combined with androgen deprivation therapy (ADT) for high-risk prostate cancer. Current retrospective series have also described an improvement in biochemical outcomes and prostate cancer-specific mortality through the use of augmented radiation strategies incorporating brachytherapy. The relative efficacy of modern augmented RT compared to RP is still incompletely understood. We present a narrative review regarding recent advances in understanding regarding comparisons of overall and prostate cancer-specific mortality measures among patients with high-risk prostate cancer treated with either an RP/adjuvant RT or an RT/ADT approach. We give special consideration to recent trends toward the assembly of multi-institutional series targeted at providing high-quality data to minimize the effects of residual confounding. We also provide a narrative review of recent studies examining brachytherapy boost and systemic therapies, as well as an overview of currently planned and ongoing studies that will further elucidate strategies for treatment optimization over the next decade.